Artists Religiosity on Social Media: Between Rules, Religious Commudification and Media Capitalism - Ulya, Inayatul; Salehudin, Ahmad (Ijtimā iyya Journal of Muslim Society Research, 2023)
This article analyzes the artist's religiosity on social media. The symbols of obedience to religion are often displayed by artists in various activities broadcasted on social media both when playing as an actor in a social media show or in their actual life that is covered on social media. The piety is shown by dressing sharia clothes, performing umrah, sponsorsing orphans program, follow Islamic sermon and others. The artist's religious expression holds the meaning, whether the motive is actually behind what is seen on social media, whether purely as part of religious obidience, or there is a religious commodification and media capitalism deliberately displayed to generate greater public viewer which subsequently increase revenue for media corporation. this study will use a phenomenological approach to understand the true meaning behind reality seen on social media. While the dramaturgy theory is used to analyze the religiousity of the artist on social media. Dramaturgy theory by Erving Goffman there is the concept of front stage and back stage. Front stage to explain the artist's visible visibility on social media, while back stage to explain the true artist's life (behind the scenes), so it can be mapped the artist's religiosity -as a religious obedience-, as part of the religious commodification or media capitalism.